2011
DOI: 10.2460/javma.238.6.773
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic pathogens isolated from wild animals and environmental samples at two California wildlife hospitals

Abstract: Potentially zoonotic enteric pathogens were identified in samples from several species admitted to wildlife hospitals, indicating potential for transmission if prevention is not practiced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 60 publications
(85 reference statements)
1
12
0
1
Order By: Relevance
“…Analysis at the GDH locus revealed that isolate HW1 was related to G. duodenalis assemblage C; in contrast, the beta-giardin locus suggested that this isolate was related to G. duodenalis assemblage D. Similar mixed multilocus genotyping results were reported in three other studies (43)(44)(45) and deserve further molecular epidemiologic investigation. Additionally, amplified DNA sequences of isolates HW4, HS71, and HC216 were detected using the GDH PCR protocol but not with the beta-giardin PCR protocol.…”
Section: Discussionsupporting
confidence: 79%
“…Analysis at the GDH locus revealed that isolate HW1 was related to G. duodenalis assemblage C; in contrast, the beta-giardin locus suggested that this isolate was related to G. duodenalis assemblage D. Similar mixed multilocus genotyping results were reported in three other studies (43)(44)(45) and deserve further molecular epidemiologic investigation. Additionally, amplified DNA sequences of isolates HW4, HS71, and HC216 were detected using the GDH PCR protocol but not with the beta-giardin PCR protocol.…”
Section: Discussionsupporting
confidence: 79%
“…Water fowl, including geese and ducks, are identified as a source of surface water and pasture contamination (107,117,118) and implicated as the source of numerous food-borne pathogens (119)(120)(121)(122). One goose is reportedly capable of producing up to 5 pounds of feces per day, and this can result in mass contamination, since these birds are usually found in flocks (123).…”
Section: Birdsmentioning
confidence: 99%
“…Mammals carry pathogens (Siembieda et al. ; Fleming & Bexton ), including rabies (Kelly & Sleeman ; Schmidt‐French et al. ).…”
Section: Research Reviewmentioning
confidence: 99%